2020
DOI: 10.1177/1369433220906226
|View full text |Cite
|
Sign up to set email alerts
|

Advanced joint slip model for single-angle bolted connections considering various effects

Abstract: Latticed structures are commonly used in transmission towers due to lightweight, fast fabrication, and easy installation, but they generally experience more complicated structural behaviors. The full-scale tests on transmission towers have revealed large discrepancies between the numerical simulation and experimental results because the significant joint slip effects have not well considered in the former. The existing joint slip models were so simple that many key parameters had not been taken into account. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Different global seed size of 5, 10 and 15 were tried for the analysis and it was found that ultimate behaviour was same for all mesh sizes and hence mesh size of 15 was adopted to minimize the computational time. Eight noded brick elements (C3D8R) with reduced integration were assigned [15], [29]. Two interactions were considered -penalty friction formulation with a friction coefficient of 0.25 in tangential behaviour and hard contacted pressure-overclosure with a penalty (Standard) for constraint enforcement method by specifying contact stiffness of 2000 Nmm with a linear behaviour [22].…”
Section: Numerical Modellingmentioning
confidence: 99%
“…Different global seed size of 5, 10 and 15 were tried for the analysis and it was found that ultimate behaviour was same for all mesh sizes and hence mesh size of 15 was adopted to minimize the computational time. Eight noded brick elements (C3D8R) with reduced integration were assigned [15], [29]. Two interactions were considered -penalty friction formulation with a friction coefficient of 0.25 in tangential behaviour and hard contacted pressure-overclosure with a penalty (Standard) for constraint enforcement method by specifying contact stiffness of 2000 Nmm with a linear behaviour [22].…”
Section: Numerical Modellingmentioning
confidence: 99%
“…In order to obtain the influence law of the axial stiffness of the joint on the stable bearing capacity of the tower, take the section sizes as A 1 = A, A 2 = A/5, A j = ζ A, respectively, the tower root opening and the height of the joints are the same, and take the height of the joints as h, that is b = h, take the two-layer tower cells as the research object, that is l = nh, n = 2, take the length coefficient of the connecting joint is k = 0.3, combined with Equation ( 14) and Equation (20), The calculation expression of the stable bearing capacity of the tower with and without the axial stiffness of the joint is obtained. The ratio coefficient of the two is taken as χ, and the expression obtained by calculation is shown in Equation (21).…”
Section: Influence Coefficient Of Axial Stiffness Of Jointsmentioning
confidence: 99%
“…Ma et al [19] conducted experimental and numerical research on the performance of the new single double transformation connection node, and further improved the existing theoretical model of gusset plate design. Abdelrahman et al [20] proposed an improved node slip model based on Numerical Simulation for the secondorder direct analysis of transmission towers. Gan et al [21] proposed a simplified joint slip model for bolted joints, and verified the theoretical model through finite element numerical simulation.…”
Section: Introductionmentioning
confidence: 99%
“…Back-to-back unsymmetrical built-up cold-formed steel (CFS) angle columns (BBUAC) are commonly used in CFS construction [1][2][3][4][5][6][7][8]. To prevent independent buckling of angle sections in such composite designs, either welds or screws are applied intermittently at specified positions along their height.…”
Section: Introductionmentioning
confidence: 99%